2018
DOI: 10.1111/dgd.12430
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organization of human iPS cells into trophectoderm mimicking cysts induced by adhesion restriction using microstructured mesh scaffolds

Abstract: Cellular dynamics leading to the formation of the trophectoderm in humans remain poorly understood owing to limited accessibility to human embryos for research into early human embryogenesis. Compared to animal models, organoids formed by self-organization of stem cells in vitro may provide better insights into differentiation and complex morphogenetic processes occurring during early human embryogenesis. Here we demonstrate that modulating the cell culture microenvironment alone can trigger self-organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Micromesh scaffolds have been used for hiPSC differentiation into trophectoderm-like cysts [19, 20]. Consistent with previously reported data, our data showed that cystic structures emerged on day 16 when using a 4-mm nickel micromesh (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Micromesh scaffolds have been used for hiPSC differentiation into trophectoderm-like cysts [19, 20]. Consistent with previously reported data, our data showed that cystic structures emerged on day 16 when using a 4-mm nickel micromesh (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Notably, micromesh-cultured hepatic cells have been shown to exhibit increased expression of hepatic marker genes and enhanced cell maturation [18]. Furthermore, Okeyo et al [19] reported that micromesh culture induces spontaneous differentiation of hiPSCs into trophoblast cyst structures without BMP4 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…40 Previous reports by Okeyo et al have shown that the hiPSCs (clone TIG1-4F hiPSC from lung fibroblasts, provided by Dr. Takashi Tada of Kyoto University, Kyoto, Japan) can differentiate into TSC-like cells. 19,20 In this study, we used the TSCs derived from the hiPSC line ChiPSC22, which is more ordinary and commercially available than the above hiPSC. Furthermore, we have been tried to obtain TSCs using the other common hiPSC lines 201B7 and 253G1, however, these hiPSC lines did not effectively differentiate into trophectoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Hori and Kurosawa reported that micromesh-cultured hepatic cells have been shown to exhibit increased expression of hepatic marker genes and enhanced cell maturation. 18 Previous reports by Okeyo et al 19,20 have shown that limited culture on micromesh can induce hiPSCs to differentiate into trophoblast cysts. Since the cells are suspended in the culture medium in a cell sheet state maintained by cell-cell adhesion, nutrition and oxygen can be supplied directly from both sides of the cell sheet.…”
mentioning
confidence: 98%
See 1 more Smart Citation